GATA 2 Deficiency: Focus on Immune System Impairment - Fabozzi, Francesco; Mastronuzzi, Angela; Ceglie, Giulia; Masetti, Riccardo; Leardini, Davide (Frontiers in Immunology, 2022)
GATA2 deficiency is a disease with a broad spectrum of clinical presentation, ranging from lymphedema, deafness, pulmonary dysfunction to miscarriage and urogenital anomalies, but it is mainly recognized as an immune system and bone marrow disorder. It is caused by various heterozygous mutations in the GATA2 gene, encoding for a zinc finger transcription factor with a key role for the development and maintenance of a pool of hematopoietic stem cells; notably, most of these mutations arise de novo. Patients carrying a mutated allele usually develop a loss of some cell populations, such as B-cell, dendritic cell, natural killer cell, and monocytes, and are predisposed to disseminated human papilloma virus and mycobacterial infections. Also, these patients have a predisposition to myeloid neoplasms, including myelodysplastic syndromes, myeloproliferative neoplasms, chronic myelomonocytic leukaemia. The age of symptoms onset can vary greatly even also within the same family, ranging from early childhood to late adulthood; incidence increases by age and most frequently clinical presentation is between the second and third decade of life. Currently, haematopoietic stem cell transplantation represents the only curative treatment, restoring both the hematopoietic and immune system function.